1993
DOI: 10.1093/mnras/261.4.883
|View full text |Cite
|
Sign up to set email alerts
|

Timing observations of southern pulsars - 1987 to 1991

Abstract: Pulse arrival-time measurements made at frequencies near 670 and 800 MHz over a 7-year period have been used to study the timing behaviour of 45 southern pulsars. These measurements have resulted in more accurate estimates of the period, period derivative, position and dispersion measure of most of these pulsars. Changes in some of the dispersion measures have been detected and used to estimate the scale-sizes and electron densities of irregularities in the interstellar medium. The timing measurements also rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 145 publications
0
22
0
Order By: Relevance
“…RX J0720.9-3125 is the first X-ray pulsar to show evidence for precession; the precession period is ∼7 yr, with correlated changes in line depth (Haberl et al 2006). Lowlevel timing "noise", seen in all pulsars, is quasi-periodic in many cases, and could represent precession at low amplitude (for examples see, e.g., Downs & Reichley 1983;and D'Alessandro et al 1993). Physically-motivated models of precession provide good fits to the data of PSR 1828-11 (Link & Epstein 2001;Akgün et al 2006) and RX J0720.9-3125 (Haberl et al 2006), supporting a precession interpretation.…”
mentioning
confidence: 84%
“…RX J0720.9-3125 is the first X-ray pulsar to show evidence for precession; the precession period is ∼7 yr, with correlated changes in line depth (Haberl et al 2006). Lowlevel timing "noise", seen in all pulsars, is quasi-periodic in many cases, and could represent precession at low amplitude (for examples see, e.g., Downs & Reichley 1983;and D'Alessandro et al 1993). Physically-motivated models of precession provide good fits to the data of PSR 1828-11 (Link & Epstein 2001;Akgün et al 2006) and RX J0720.9-3125 (Haberl et al 2006), supporting a precession interpretation.…”
mentioning
confidence: 84%
“…It manifests as noise in phase, frequency, or frequency derivative in different objects [125][126][127]. In general the effects can be due to various processes including precession [128,129], Tkachenko modes [130], superfluid vortex creep [25], superfluid turbulence [103], or changes in the magnetic field [101,110,131]. Timing noise is of interest for the current discussion as it has been suggested that glitches below the observational threshold may be the cause of timing noise [25,132] and of the measurement of anomalous breaking indices [133,134].…”
Section: Timing Noisementioning
confidence: 99%
“…It has now been widely observed (Boynton et al 1972;D'Alessandro et al 1993;Chukwude 2002) that the m = 3 polynomial model appears to describe the observations of most pulsars significantly better than the m = 2 model, in that both the rms phase residuals and the reduced chi-squares are significantly less for the third-order model. However, there is still controversy over whether the m = 3 polynomial models offer a better description of the intrinsic pulsar spin-down instead of just merely absorbing fluctuations in the pulsar spin rates.…”
Section: Introductionmentioning
confidence: 98%